Antibacterial and antibiofilm activities of star anise-cinnamon essential oil against multidrug-resistant Salmonella Thompson - Zhang, Jie; Zhang, Dapei; Chen, Yanhua; Gong, Yongyu; Yuan, Binfang; Mo, Zhiyuan; Tang, Haibo; Tao, Junyu; Xu, Ziheng (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe emergence of foodborne multidrug-resistant (MDR) Salmonella has attracted considerable global attention. Given that food is the primary transmission route, our study focuses on Bellamya quadrata, a freshwater snail that is commonly consumed as a specialty food in Guangxi, China.MethodsEight MDR Salmonella strains were isolated from Bellamya quadrata samples collected across various markets. Previous animal experiments have confirmed their lethality in mice. We determined the minimum inhibitory concentrations (MICs) and fractional inhibitory concentration (FIC) indices of cinnamon essential oil (CEO) and star anise essential oil (SAEO) using the microdilution plate and checkerboard methods. The time-kill curve method was employed to assess the antibacterial activity of the cinnamon-star anise essential oil (SCEO) against planktonic MDR Salmonella. The alkaline phosphatase assay and fluorescence microscopy demonstrated that SCEO causes damage to bacterial cell walls and membranes. Crystal violet staining and scanning electron microscopy (SEM) were used to observe changes in biofilms after SCEO treatment. Quantitative real-time PCR was utilized to analyze the expression of genes related to biofilm formation following SCEO treatment.ResultsThe MIC of SAEO was determined to be 25 mg/mL, whereas that of CEO was significantly lower at 0.62 mg/mL. The FIC index calculated was 0.375, which suggests a synergistic interaction between the two. When SCEO was used in combination at specific ratios, it demonstrated enhanced antibacterial and anti-biofilm capabilities compared to the individual effects of CEO or SAEO, potentially through the disruption of bacterial cell membranes and cell walls. However, in Salmonella treated with SCEO, an upregulation in the expression of biofilm-associated genes was observed, including csgA, adrA, bcsA, and csgD. This increase may be attributed to stress-induced transcriptional responses within the bacteria.DiscussionSCEO significantly impacts cell wall integrity, suggesting its crucial role in reducing biofilm formation. These findings indicate that SCEO holds potential as an alternative to traditional antibiotics and merits further scientific investigation and development.